Development of a Learning Media Based on E-Comics - Khairunnisa, Sinta; Maspupah, Meti; Suhada, Idad (KnE Social Sciences, 2024)
The results of a preliminary study conducted on a Biology teacher and students of Class X Science 2 showed that WhatsApp was the most regularly used communication media. This is considered to be less effective, resulting in the learning becomes not optimal. During the pandemic, one of the learning media which could have been used was e-comic. This could be accessed through Instagram. Thus, this study aimed to develop and assess the feasibility of Instagram-assisted e-comic learning media. The development model used was 3-D: define, design, and develop. This development research was carried out at 24 Senior High School Bandung. The research subjects consisted of 3 expert validators and 18 students of class Class X Science 2. This development research used assessment questionnaires for validators and respondent questionnaires for students. The results of the validation with the revision process based on the advice of chapter experts show that this learning media is very valid with a combined score of 89.80%, and the results of the questionnaire of product trial respondents to the students got a very good category of feasibility with a score of 4.4. Keywords: development, learning, media, e-comics